2006
DOI: 10.1038/sj.mp.4001798
|View full text |Cite
|
Sign up to set email alerts
|

The Dimensional Yale–Brown Obsessive–Compulsive Scale (DY-BOCS): an instrument for assessing obsessive–compulsive symptom dimensions

Abstract: Obsessive-compulsive disorder (OCD) encompasses a broad range of symptoms representing multiple domains. This complex phenotype can be summarized using a few consistent and temporally stable symptom dimensions. The objective of this study was to assess the psychometric properties of the Dimensional Yale-Brown Obsessive-Compulsive Scale (DY-BOCS). This scale measures the presence and severity of obsessive-compulsive (OC) symptoms within six distinct dimensions that combine thematically related obsessions and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
245
3
21

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(278 citation statements)
references
References 53 publications
9
245
3
21
Order By: Relevance
“…26 It has been shown to have excellent psychometric properties. 26 The instrument consists of 88 examples of OC symptoms, 26 accompanied by questions that assess their severity.…”
Section: Evaluation Of Oc Symptom Dimensions 1) Dy-bocsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 It has been shown to have excellent psychometric properties. 26 The instrument consists of 88 examples of OC symptoms, 26 accompanied by questions that assess their severity.…”
Section: Evaluation Of Oc Symptom Dimensions 1) Dy-bocsmentioning
confidence: 99%
“…26 It has been shown to have excellent psychometric properties. 26 The instrument consists of 88 examples of OC symptoms, 26 accompanied by questions that assess their severity. The severity scores, divided into current and "worst-ever" scores, are based on how much patient time is lost in dealing with OC symptoms, as well as on the level of patient distress caused by those symptoms and the degree to which they impair patient quality of life.…”
Section: Evaluation Of Oc Symptom Dimensions 1) Dy-bocsmentioning
confidence: 99%
“…Factor analytic studies regarding the clinical manifestations of OCD identified the following main symptom dimensions: symmetry/ordering, hoarding, contamination/cleaning, aggressive obsessions/checking, and sexual/religious obsessions [3]. Indeed, the identification of OCD subtypes may facilitate genetic, neurobiological, and treatment studies [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Inter-rater reliability and test-retest (YBOCS) to assess the symptoms of OCD, but not in other disorders and depression have been reported suitable (Woody, Steketee, & Chambless, 1994;Tek, Ulu, & Gürsoy Rezaki, 1995). (Y-BOCS) was translated into 13 languages, and the reliability and validity of this scale in the research (Calamari, Wiegartz, & Janeck,1999;Moritz, Meie, & Kloss, 2002;Arrindell, Vlaming, Eisenhardt, & Berkum, 2002;Feinstein, Fallon, Petkova, & Liebowitz, 2003;Deacon, & Abramowitz, 2005;Storch, Shapira, Dimoulas, Geffken, & et al,2005;Rosario-Campos, Miguel, Quatrano, Chacon, & et al,2006;Stein, Andersen, & Overo, 2007;Cullen, & Brown, 2007; and many cultures (Mollard, Cottraux, & Bouvard, 1989;Nakajima, 1999;Woody, Steketee, & Chambless,1994;Rosas, Vega-Dienstmaier, Suarez, Vidal, & et al,2002;Jacobsen, Kloss, Fricke, Hand, & et al,2003) have been studied. In Iran only 3 study (Mohammad-khani, 1991;Bigham, 2000;Rajezi-Esfahani, Motaghipour, Kamkari, MCSER Publishing, Rome-Italy Vol 6 No 4 S2 July 2015 175…”
Section: Methodsmentioning
confidence: 99%